Scratching the structure of moral agency: insights from philosophy applied to neuroscience - Castro-Toledo, Francisco Javier; Cerezo, Pablo; Gómez-Bellvís, Ana Belén (Frontiers in Neuroscience, 2023)
This paper explores the intersection between neuroscience and philosophy, particularly in the areas of moral philosophy and philosophy of mind. While traditional philosophical questions, such as those relating to free will and moral motivation, have been subject to much debate, the rise of neuroscience has led to a reinterpretation of these questions considering empirical evidence. This has led to tensions between those who believe neuroscience can provide definitive answers to very complex philosophical questions and those who are sceptical about the scope of these studies. However, the paper argues that neuroscientists and philosophers can work together to generate major scientific and social advances. To contribute to bridge the gap, in this paper we expose the complexity of moral experience from a philosophical point of view and point to two great challenges and gaps to cover from neurosciences.